2016
DOI: 10.3852/15-090
|View full text |Cite
|
Sign up to set email alerts
|

Understanding lichenicolous heterobasidiomycetes: new taxa and reproductive innovations in Tremella s.l.

Abstract: Four new lichenicolous Tremella species are described and characterized morphologically and molecularly. Tremella celata grows on Ramalina fraxinea, inducing the formation of inconspicuous galls, and having hyphae with incomplete clamps. Tremella endosporogena develops intrahymenially in the apothecia of Lecanora carpinea, having single-celled basidia and clampless hyphae. Tremella diederichiana is the name proposed for a species micromorphologically close to T. christiansenii but inducing the formation of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
2
33
0
1
Order By: Relevance
“…Simple, 1-spored basidia are highly unusual in the Basidiomycota , and in most cases species characterised by 1-spored basidia belong to genera with a variable number of spores produced per basidium, e.g., Heteroacanthella , Lactarius , Oliveonia , Russula , Septobasidium , and Tremella s.lat. ( Zamora et al 2014 , 2016 , Vidal et al 2019 ). This result, together with the phylogenetic position of Dacryonaema , allowed inferring the bisterigmate basidium as the most probable ancestral state for the Dacrymycetes in most analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Simple, 1-spored basidia are highly unusual in the Basidiomycota , and in most cases species characterised by 1-spored basidia belong to genera with a variable number of spores produced per basidium, e.g., Heteroacanthella , Lactarius , Oliveonia , Russula , Septobasidium , and Tremella s.lat. ( Zamora et al 2014 , 2016 , Vidal et al 2019 ). This result, together with the phylogenetic position of Dacryonaema , allowed inferring the bisterigmate basidium as the most probable ancestral state for the Dacrymycetes in most analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of Tremella s. lat. species grow on lichens (Diederich 1986(Diederich , 1996(Diederich , 2003(Diederich , 2007Diederich & Marson 1988;Diederich & Christiansen 1994;Sérusiaux et al 2003;Zamora et al 2011Zamora et al , 2016Millanes et al 2012Millanes et al , 2014aDiederich et al 2014). These taxa are, just like many other Tremella species, mycoparasites, and no interactions with the host lichen photobiont algae have been observed (Grube & de los Ríos 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, since recent studies have shown that host specificity is important to characterize certain evolutionary lineages in this group of fungi (Millanes et al 2014b;Zamora et al 2016), T. anaptychiae has to be compared with the other Tremella species known to parasitize Caliciales hosts. None of them is morphologically similar to T. anaptychiae, since T. phaeophysciae and T. rinodinae Diederich & M.S.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological study was based on nine specimens collected either by the authors or collaborators. General methodology and terminology follows Diederich (1996) and Zamora et al (2016). Micromorphological study was done using hand-cut sections mounted and stained with Congo red in 10% ammonia, phloxin B in 5% KOH or a mixture of Congo red and phloxin B in 5% KOH.…”
Section: Morphologymentioning
confidence: 99%